Left main coronary artery disease: percutaneous coronary intervention or coronary artery bypass grafting? A critical review of current knowledge and contemporary debates - Ioannis Panagiotopoulos; Francesk Mulita; Georgios-Ioannis Verras; Eleni Bekou; Admir Mulita; Manfred Dahm; Konstantinos Grapatsas; Assaf Sawafta; Anastasia Katinioti; Elias Liolis; Christos Pitros; Levan Tchabashvili; et al. (Termedia Publishing House, 2024)
Significant unprotected left main (ULM) disease is the highest-risk coronary artery lesion, carries high morbidity and mortality related to a large amount of myocardium supplied, and should undergo prompt revascularization. Among recent randomized controlled trials (RCTs), NOBLE failed to demonstrate non-inferiority of percutaneous coronary intervention (PCI) versus coronary artery bypass grafting (CABG). However, all the other RCTs have shown comparable outcomes. While CABG is associated with higher stroke rates at 30 days and 1 year, PCI is associated with increased spontaneous myocardial infarction (MI) events and the need for repeat revascularization. Furthermore, the benefit of CABG is more evident with the increased complexity of coronary artery disease. In current European and American guidelines, CABG is the standard of care for ULM disease. PCI is considered a reasonable alternative in selected patients (2a B-NR). There is still a great need for carefully designed RCTs with longer follow-up times to validate the role of recent technological and pharmacological regimens.